Does lactate enhance the prognostic accuracy of the quick Sequential Organ Failure Assessment for adult patients with sepsis? A systematic review - Ling Li; Vincent Lam; Clifford Hughes; Angus Gill; Khalia Ackermann (BMJ Open, 2022)
Objectives To investigate whether adding lactate to the quick Sequential (sepsis-related) Organ Failure Assessment (qSOFA) improves the prediction of mortality in adult hospital patients, compared with qSOFA alone.Design Systematic review in accordance with Preferred Reporting Items for a Systematic Review and Meta-analysis of Diagnostic Test Accuracy Studies guidelines.Data sources Embase, Medline, PubMed, SCOPUS, Web of Science, CINAHL and Open Grey databases were searched in November 2020.Eligibility criteria Original research studies published after 2016 comparing qSOFA in combination with lactate (LqSOFA) with qSOFA alone in adult patients with sepsis in hospital. The language was restricted to English.Data extraction and synthesis Title and abstract screening, full-text screening, data extraction and quality assessment (using Quality Assessment of Diagnostic Accuracy Studies-2) were conducted independently by two reviewers. Extracted data were collected into tables and diagnostic test accuracy was compared between the two tests.Results We identified 1621 studies, of which 11 met our inclusion criteria. Overall, there was a low risk of bias across all studies. The area under the receiver operating characteristic (AUROC) curve for qSOFA was improved by the addition of lactate in 9 of the 10 studies reporting it. Sensitivity was increased in three of seven studies that reported it. Specificity was increased in four of seven studies that reported it. Of the six studies set exclusively within the emergency department, five published AUROCs, all of which reported an increase following the addition of lactate. Sensitivity and specificity results varied throughout the included studies. Due to insufficient data and heterogeneity of studies, a meta-analysis was not performed.Conclusions LqSOFA is an effective tool for identifying mortality risk both in adult inpatients with sepsis and those in the emergency department. LqSOFA increases AUROC over qSOFA alone, particularly within the emergency department. However, further original research is required to provide a stronger base of evidence in lactate measurement timing, as well as prospective trials to strengthen evidence and reduce bias.PROSPERO registration number CRD42020207648.